The Problems, Issues and Challenges of Planning Education in Indonesia - Mochtarram Karyoedi (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
This article is intended to describe the current development of planning education in Indonesia and will consist of 3 main issues as follows: Firstly, a quick look at the dynamic of national, regional and local planning development concept and practice, and in line with the need of Indonesian development program this paper is also intended to explore the importance and need of planning education, and lastly this paper is going to discuss the development of planning education in Indonesia.